Understanding the recent invasion in Cacosceles newmannii (Coleoptera: Cerambycidae) into sugarcane from a thermal perspective - (:unkn) unknown (My University, 2018)
The recent invasion of the indigenous longhorn beetle Cacosceles newmannii (Coleoptera:Cerambycidae) into sugarcane of KwaZulu-Natal has resulted in widespread concern surrounding its pest status and further potential for spread and damage in surrounding sugarcane crops. Its dramatic host shift from indigenous vegetation can be attributed to several potential mechanisms, including abiotic and biotic factors. The thermal limits to activity and survival of larvae and adults in a set of laboratory experiments are examined, and a predominant hypothesis about the cause of high temperature death (i.e. oxygen limitation theory) is tested. We also report on mortality rate across a range of temperatures of C. newmannii on sugarcane and artificial diet. Thermal trait information is then integrated with what is known about sugarcane environments in KwaZulu-Natal and supply the first step in forecasting the potential spread of this longhorn beetle.
Keywords: African Research